Conceptual Model for Predicting Academic Success in Prelicensure Nursing Programs Through Expanded Cognitive Aptitude Assessment. Issue 6 (November 2019) - Twidwell, Julie; Sanner-Stiehr, Ericka; Allen, Kimberly; Records, Kathie; Hsueh, Kuei-Hsiang
Abstract : Background: Attrition from prelicensure nursing programs is a serious issue with implications for students, nursing programs, and the nursing workforce. Academic failure due to insufficient cognitive aptitude often contributes to this problematic attrition rate. Thus, cognitive aptitude could be included in admission criteria, as a predictor of academic success and a strategy to minimize attrition. Problem: Currently, admissions practices are often incomplete and lack standardization for measuring cognitive aptitude. Approach: The Nursing Cognitive Aptitude Model (NCAM) presented in this article is an innovative conceptual model to guide educators in expanding current admissions processes. Conclusion: The NCAM model depicts the cognitive domains involved in student academic success including current scholastic knowledge, previous academic performance, and critical-thinking ability. Together, these three domains predict student academic success and are a useful reference for the admissions process. Abstract : Supplemental digital content is available in the text.